The Effect Of Zinc Dialkyldithiophosphate Addition To Corn Oil In Suppression Of Oxidation As Enhancement For Bio Lubricants : A Review - Azhari, Muhamad Azwar; Suffian, Quratul Nadia; Mat Nuri @ Md Din, Nur Rashid (Asian Research Publishing Network (ARPN), 2014)
-